Local and systemic erythropoietin levels in complicated proliferative diabetic retinopathy - V. V. Neroev; O. V. Zaitseva; Z. V. Kurchaeva; O. S. Slepova (Российский офтальмологический журнал, 2018)
The levels of erythropoietin (EPO) in biological fluids were studied on 43 patients with diabetes mellitus type I and II who suffered from a variety of clinical manifestations of heavy proliferative diabetic retinopathy (PDR) which incuded stable PDR, 12 patients with rhegmatogenous retinal detachment and 15 healthy individuals The correlation of EPO levels with the clinical features of heavy PDR was noted only at the local level (intravitreally). The highest intraocular levels of EPO were associated with severe features of the disease, abundant vascularizarion of fibroglial tissue, and intraoperative hemorrhagic complications, which corroborates the theory of active participation of locally secreted EPO in ocular neoangiogenesis, including the progression of PDR // Russian Ophthalmological Journal, 2016; 2: 55-60. doi: 10.21516/2072-0076-2016-9-2-55-60 .